Author Correction: Accuracy and Precision of Tidal Wetland Soil Carbon Mapping in the Conterminous United States. Issue 1 (December 2018) - Holmquist, James; Windham-Myers, Lisamarie; Bliss, Norman; Crooks, Stephen; Morris, James; Megonigal, J.; Troxler, Tiffany; Weller, Donald; Callaway, John; Drexler, Judith; Ferner, Matthew; Gonneea, Meagan; et al.
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has not been fixed in the paper.